DISCOURSE MARKERS USED BY STUDENTS IN NONFORMAL EDUCATION - Nurul . Atikah; Amrin . Saragih; Zainuddin . Zainuddin (Universitas Negeri Medan, 2022)
It is very common to acknowledge that in order to achieve a good communication, discourse markers are needed as one of a tool to perform in linking the ideas to ideas, especially in spoken language, it’s really helpful in guiding the speakers and listeners to comprehend what is being discussed or talked. There are several studies has been discussed about what discourse markers are especially in spoken language, but in this research, the realization of discourse markers is the aim of the study. The data source of this research were students in Harford Institute Sekip Branch, there were 16 students taken from 4 different levels and they were taken by using purposive sampling. The data were the words from their utterances which contains of discourse markers which were collected by using audio recorder. And the research was done by applying descriptive qualitative method. The result revealed that there are 3 realizations based on the position found in Discourse Markers, they are at the boundary (Initial), after the first word (Middle) and later (Final), where initial discourse markers appeared as the most dominant one. It is proved that the discourse marker realized in the Initial position to signal upcoming information, since discourse markers has the essential function to connect or link ideas to the ideas or even as a pause in the speech. Keywords: Discourse Markers, Students Interactions, NonformalEducation